The Danish-Friendly Environment And Human Rights Business: A Human Rights-Based Perspective On Economic Development And Business Activities Address The Problem Of Climate Change - Yustin Olivia Kadmayer (Kybernology : Journal of Government Studies, 2022)
This paper aims to find address the problem of climate change through the Danish-friendly environment and human rights business. The biggest causes for climate change derive from aggressive business and human being activities. The impacts of climate change are direct and indirect linked to human rights. Denmark is categorized as the most friendly environment country in 2022. This achievement is a reward for Denmark which has had a development climate policy since the 70s through the green energy transition. Denmark developed its climate policy into business. The business is a friendly-environment and human rights. The development theory is implemented in this paper to answer the development of the Danish climate policy.